1996
DOI: 10.1053/gast.1996.v110.pm8613052
|View full text |Cite
|
Sign up to set email alerts
|

Selective kallikrein-kinin system activation in inbred rats differentially susceptible to granulomatous enterocolitis

Abstract: Selective in vivo and in vitro activation of the contact system in susceptible Lewis rats suggests that this pathway is one determinant of genetic susceptibility to granulomatous enterocolitis and systemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…account for at least half of the diversity of bacteria in the colon (64,65). In genetically susceptible rats, intramural injection of PGN results in granulomatous inflammatory bowel disease (66,67). Animal models of inflammatory bowel disease such as the IL-10 knockout mouse reconstituted with Gram-positive Enterococcus faecalis develop chronic intestinal inflammation (68,69).…”
Section: Human Intestinal Epithelial Cells Are Broadly Unresponsive Tmentioning
confidence: 99%
“…account for at least half of the diversity of bacteria in the colon (64,65). In genetically susceptible rats, intramural injection of PGN results in granulomatous inflammatory bowel disease (66,67). Animal models of inflammatory bowel disease such as the IL-10 knockout mouse reconstituted with Gram-positive Enterococcus faecalis develop chronic intestinal inflammation (68,69).…”
Section: Human Intestinal Epithelial Cells Are Broadly Unresponsive Tmentioning
confidence: 99%
“…Furthermore, the involvement of the kallikrein-kinin system in the development of experimental IBD models that mimic human Crohn's disease was also reported (8,9,35). Although it was reported that the activation of the plasma kallikrein-kinin system was evaluated from the consumption of plasma prekallikrein and high-molecularweight kininogen (8,35), the actual contribution of kinins to enterocolitis should be tested using adequate biological and pharmacological approaches (36).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in spite of the potent proinflammatory activity of kinins, the involvement of the kallikrein-kinin system in the development of experimental enterocolitis (8,9,22) and colitis (4) has been demonstrated, but the number of reports is limited. In a model of granulomatous enterocolitis induced in a genetically susceptive strain of Lewis rats by peptidoglycan-polysaccharide polymers isolated from group A streptococci, the activation of the plasma kallikrein kinin system was presumed to have occurred, because of the consumption of the precursor proteins plasma prekallikrein and high-molecular-weight kininogen (9, 23 -25).…”
mentioning
confidence: 99%
“…8 The Lewis rat is clearly more susceptible to develop chronic intestinal and systemic inflammation than the Buffalo and the Fischer 344 rat. 9 However, the genes involved in these differences have not yet been identified. We developed a rat model of chronic granulomatous enterocolitis by injecting purified bacterial cell wall polymers, peptidoglycan polysaccharide from group A streptococci (PG-APS), into the intestinal wall.…”
Section: Introductionmentioning
confidence: 99%
“…Female Lewis rats, the highest responders, develop biphasic intestinal inflammation with an acute phase that peaks 2 to 4 days after PG-APS injection and gradually decreases over the next 10 days. 9,13 The enterocolitis spontaneously reactivates on days 12 to 14 accompanied by T-lymphocytemediated peripheral erosive arthritis, granulomatous hepatitis, normochromic anemia, and leukocytosis.…”
Section: Introductionmentioning
confidence: 99%